Penentuan Kadar Total Fenol dan Uji Aktivitas Antioksidan Ekstrak Etanol Daun Kelor (Moringa oleifera L.) dengan Metode DPPH - Lampita Bellina Manullang; Razoki Razoki; Roy Indrianto Bangar (Herbal Medicine Journal, 2026)
This study aimed to determine the total phenolic content and evaluate the antioxidant activity of the ethanolic extract of Moringa oleifera L. Extraction was carried out using the maceration method with 96% ethanol. Total phenolic content was determined using the Folin–Ciocalteu method with gallic acid as the standard, while antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH. assay and expressed as IC₅₀ values. The results showed that the ethanolic extract of Moringa oleifera leaves contained an average total phenolic content of 69.126 mg gallic acid equivalents per gram of extract. The antioxidant activity test yielded an IC₅₀ value of 92.04 ppm, indicating strong antioxidant activity. The high phenolic content contributed to the extract’s ability to scavenge free radicals. These findings suggest that the ethanolic extract of Moringa oleifera leaves has potential as a natural antioxidant source.